Structure and genetic diversity of three Calibrachoa caesia populations by ISSR markers - Perez De La Torre, Mariana; Escandon, Alejandro Salvio; Heinz, Ruth Amelia (ISHS, 2018)
Calibrachoa caesia is one of thirteen native species of the genus Calibrachoa Cerv. ex La Lave et Lexarza (Solanaceae) growing in Argentina. The genus has a high ornamental value due to the morphological variability that it shows for different genetic characters, including the flower colors. The structure and variation of 29 accessions from populations of three departments in the Province of Misiones (Oberá, Guaraní and San Ignacio) were analyzed by Inter simple sequence repeat (ISSR) markers. Thirteen ISSR primers produced reproducible bands, with 652 amplified and 97.4% polymorphism. The polymorphism information content ranged from 0.144 to 0.170 for accessions from San Ignacio and Oberá populations, being the average 0.158, whereas the Shannon Index showed an average of 0.256. The principal coordinate analysis showed that the San Ignacio individuals were more disperse than the Guaraní and Oberá accessions. The analysis of molecular variance (AMOVA) test for Guaraní, Oberá and San Ignacio populations, showed highest genetic variation within populations (93.59%), meanwhile the Fst coefficient was 0.064, indicating a low to medium differentiation between populations, showing a great intrapopulation genetic diversity but no significant difference was detected among San Ignacio, Oberá and Guaraní populations. According to these results, the highly polymorphic level of the 29 analyzed individuals from the three locations represents an important source of genetic variability for future breeding programs